The influence of the principal instructional leadership of theacer's job satisfaction at vocational secondary schools - Hermi Kurnia; Nurtanio Agus Purwanto; Indah Fitoriyati (Jurnal Pendidikan Vokasi, 2021)
This study aimed to discover the school principal instructional leadership influence on job satisfaction of vocational high school teachers in Sleman Regency, D.I. Yogyakarta. This type of research was ex-post facto with a quantitative approach. The questionnaire was conducted on 91 teachers (71,09% response rate) to examine the influence of principal instructional leadership (X) on teacher job satisfaction (Y). Validation of the instrument used expert judgment and empirical test with the Pearson Product Moment correlation, 43 out of 43 items are declared valid. The instrument reliability test was applied by using Cronbach's Alpha. The results of the reliability test showed that all variables were declared reliable (Î± > 0,7). A classical assumption test was done by testing normality, linearity, multicollinearity, and heteroscedasticity. Simple linear regression was used as data analysis to test the influence of the independent variable (X) towards the dependent variable (Y). The simple linear regression results indicate a positive and significant influence between the principal instructional leadership on teacher job satisfaction (t = 13,329, p = .000). The coefficient of determination value (R^2)  of 0,666 indicates that the principal instructional leadership influences teacher job satisfaction by 66,6%. Meanwhile, the remaining 33,4% are influenced by other factors.